Online-Based Civic Education Learning During the Covid-19 Pandemic - Farida (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2021)
This study examines the implementation of online learning at SMP Negeri 1 Tondon. The research focuses on the use of various applications, such as WhatsApp, Google Classroom, Google Meet, and Zoom, in delivering online lessons. The factors affecting online learning at the school are analyzed, including technology, teacher characteristics, and student characteristics. The findings highlight the challenges faced in terms of internet access, insufficient government assistance in providing internet quotas, and the need for improved technological skills among students. The study also emphasizes the importance of effective planning, diverse learning media, and strategies to enhance student participation in online classes. Recommendations are proposed to address these challenges, including the need for equitable internet access in remote areas, adequate government support, and awareness and readiness from both teachers and students. The study contributes to a better understanding of the implementation of online learning and offers insights for improving its effectiveness in SMP Negeri 1 Tondon.